Magnetic resonance for wireless power transfer - Hui,SYR (IEEE Power Electronics Magazine, 2016)
Magnetic resonance has been a cornerstone of nonradiative wireless power transfer (WPT) since the late 19th century. However, some researchers have the misconception that magnetic resonance for WPT was developed recently. This article traces some early work of Tesla and other researchers related to the use of magnetic resonance in WPT. Included are some examples of magnetic resonance-based WPT projects conducted by researchers in the biomedical and power electronics communities over the last few decades. Two principles used in WPT are reiterated in this article, and their advantages and disadvantages are addressed. Some issues that may affect future trends of short- and midrange applications are discussed.